The Emergence of Universal Immune Receptor T Cell Therapy for Cancer - Minutolo, Nicholas G.; Hollander, Erin E.; Powell, Daniel J. (Frontiers in Oncology, 2019)
Chimeric antigen receptor (CAR) T cells have shown great success in the treatment of CD19+ hematological malignancies, leading to their recent approval by the FDA as a new cancer treatment modality. However, their broad use is limited since a CAR targets a single tumor associated antigen (TAA), which is not effective against tumors with heterogeneous TAA expression or emerging antigen loss variants. Further, stably engineered CAR T cells can continually and uncontrollably proliferate and activate in response to antigen, potentially causing fatal on-target off-tumor toxicity, cytokine release syndrome, or neurotoxicity without a method of control or elimination. To address these issues, our lab and others have developed various universal immune receptors (UIRs) that allow for targeting of multiple TAAs by T cells expressing a single receptor. UIRs function through the binding of an extracellular adapter domain which acts as a bridge between intracellular T cell signaling domains and a soluble tumor antigen targeting ligand (TL). The dissociation of TAA targeting and T cell signaling confers many advantages over standard CAR therapy, such as dose control of T cell effector function, the ability to simultaneously or sequentially target multiple TAAs, and control of immunologic synapse geometry. There are currently four unique UIR platform types: ADCC-mediating Fc-binding immune receptors, bispecific protein engaging immune receptors, natural binding partner immune receptors, and anti-tag CARs. These UIRs all allow for potential benefits over standard CARs, but also bring unique engineering challenges that will have to be addressed to achieve maximal efficacy and safety in the clinic. Still, UIRs present an exciting new avenue for adoptive T cell transfer therapies and could lead to their expanded use in areas which current CAR therapies have failed. Here we review the development of each UIR platform and their unique functional benefits, and detail the potential hurdles that may need to be overcome for continued clinical translation.